Fitting in, figuring it out: Attitudes to English at a South African university - O’Shea, Cathy (Journal for Language Teaching, 2025)
Students at South African higher education institutions typically need to use English as their language of learning and teaching. One of the objectives of this study was to explore what students felt about this, and how their perceptions and practices were linked to their identities. Small focus group discussions were held with students at a South African university. A framework of New Literacy Studies was used, which views student learning as a process of mastering discipline-specific, socially constructed norms and values, and sees the adoption of any kind of literacy as including the adoption of an identity. Critical Discourse Analysis was then applied to the transcripts of these discussions. Two of the Discourses revealed in this way were the ‘Model C was better’ and the ‘English to fit in’ Discourse. The former was a Discourse of deficit, with students attributing academic success to those who experienced ‘good’ schooling from ex-Model C schools and so were proficient in English. ‘English to fit in’, by contrast, was a Discourse underpinned by quiet pride in the students’ own multilingualism. It is argued that deficit discourses need to be noted and, if possible, countered, if efforts to improve students’ levels of academic literacy are to succeed.